Aromaticity in Pericyclic Transition State Structures? A Critical Rationalisation Based on the Topological Analysis of Electron Density. Issue 18 (15th November 2016) - Domingo, Luis R.; Ríos‐Gutiérrez, Mar; Chamorro, Eduardo; Pérez, Patricia
Abstract: The nature of the electron delocalisation pattern within a cyclic structure, i. e. the aromatic character, is examined for six‐membered pseudocyclic transition state structures (TSs) involved in five representative examples of so‐called pericyclic reactions. Results of the electron localisation function (ELF) and the quantum theory of atoms in molecules (QTAIM) analyses of the electron density evidence that in four of the cases, at least one pair of atoms are not bound at the TS configuration, thus precluding a possible cyclic conjugation. These findings make it possible to rule out the aromatic character of these TSs. High values of the synchronicity Sy index at the TSs contrast with the bonding changes evidenced by ELF topological analysis. The magnitude of the nucleus independent chemical shift (NICS) computed for the five TSs becomes much more negative than that of the reference system, benzene, with no obvious relation to the strong evidence of the pattern of delocalisation revealed by the topological analysis of ELF and QTAIM for each TS. The topology of the anisotropy of current induced density (ACID) at each TS reveals the actual existence of strong non‐symmetrical patterns of electron delocalisation of the five TSs. Abstract : The molecular electron density, the electron localisation function (ELF) and the quantum theory of atoms in molecules (QTAIM) analyses evidence that at least in three of the studied pseudocyclic reactions, one pair of atoms are not bound at the transition state structure, thus precluding a possible cyclic conjugation, and consequently an aromatic character.